Two different approaches for novel extracapsular cranial cruciate ligament reconstruction: an in vitro kinematics study. (25th March 2015) - Cinti, F.; Signorelli, C.; Lopomo, N.; Baracchi, M.; Del Magno, S.; Foglia, A.; Zaffagnini, S.; Pisoni, L.
<x xml:space="preserve">Abstract</x> OBJECTIVE To analyse the best combination of isometric points with the best kinematic results between two different approaches of TightRope® cranial cruciate ligament reconstruction. MATERIALS AND METHODS Cranial drawer, cranial tibial thrust, internal/external, range of motion and varus/valgus tests were passively performed in different stifle conditions: cranial cruciate ligament‐intact/deficient, after F2‐T2/F2‐T3 TR reconstruction at 22‐44‐99 N of tension. Data were acquired by a custom‐made navigation system. RESULTS The cranial drawer test showed recovery of laxity only at 99 N in both approaches. Significant laxity reduction (cranial tibial thrust) was present at only the F2‐T2 point. Differences were noted in internal/external and varus/valgus rotation between the cranial cruciate ligament‐intact and TightRope® stifles at all of the implant tensions. The range of motion underlined significantly lower laxity values following the F2‐T2/F2‐T3 reconstruction at all of the evaluated implant tensions. CLINICAL SIGNIFICANCE The best isometric site was at the F2‐T2 point, however significant differences in the amount of laxity between the two techniques were limited to the cranial tibial thrust and internal/external test. The F2‐T2 technique was the best consideration for clinical application because it is relatively easy to perform, repeatable and results in good stifle stability with low morbidity and complications.